2004
DOI: 10.1007/s00442-004-1783-0
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to the solution of the linear mixing model for a single isotope: application to the case of an opportunistic predator

Abstract: Mixing models are used to determine diets where the number of prey items are greater than one, however, the limitation of the linear mixing method is the lack of a unique solution when the number of potential sources is greater than the number (n) of isotopic signatures +1. Using the IsoSource program all possible combinations of each source contribution (0-100%) in preselected small increments can be examined and a range of values produced for each sample analysed. We propose the use of a Moore Penrose (M-P) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…A 4-prey mixing model incorporating a Moore-Penrose pseudoinverse analysis (Hall-Aspland et al 2005) was applied to vibrissae δ 15 N values from Antarctic seals A, B 1 , B 2 and C 1 to determine the proportions of prey consumed. The method is applicable to the case of a single isotope, in this case nitrogen N, and a set of mixing fractions (f 1 , f 2 , ..., f k , ..., f n ) associated with a set of prey isotopic signatures (δ 15 N 1 , δ 15 N 2 , ..., δ 15 N k , ..., δ 15 N n ), which are assumed to produce a mixture δ 15 N Mix for the prey.…”
Section: Methodsmentioning
confidence: 99%
“…A 4-prey mixing model incorporating a Moore-Penrose pseudoinverse analysis (Hall-Aspland et al 2005) was applied to vibrissae δ 15 N values from Antarctic seals A, B 1 , B 2 and C 1 to determine the proportions of prey consumed. The method is applicable to the case of a single isotope, in this case nitrogen N, and a set of mixing fractions (f 1 , f 2 , ..., f k , ..., f n ) associated with a set of prey isotopic signatures (δ 15 N 1 , δ 15 N 2 , ..., δ 15 N k , ..., δ 15 N n ), which are assumed to produce a mixture δ 15 N Mix for the prey.…”
Section: Methodsmentioning
confidence: 99%
“…ISOSOURCE samples across all possible resource combinations at user-defined intervals, identifies any points producing isotope values consistent with the observed mixture, and then summarizes the distribution of those valid points (mean, standard deviation, ranges, etc.). This allows researchers to model resource contributions in circumstances where no unique solution exists (e.g., Benstead et al, 2006;Codron et al, 2009;Hall-Aspland et al, 2005;Urton and Hobson, 2005;Coltrain, 2009). SISUS achieves the same end in a more efficient and accurate way, analyzing multiple mixtures simultaneously and allowing for differences in isotopic enrichment factors, source concentration, and assimilation efficiency (Erhardt, 2007(Erhardt, , 2010.…”
Section: Sisusmentioning
confidence: 99%
“…The IsoSource model has been employed in recent food web studies (Hall-Aspland et al 2005;Benstead et al 2006;Gerardo Herrera et al 2006;Herwig et al 2007), but the utilization of IsoSource to approach the issue of contaminant transfer in food webs is far less common. In our study, we found a correlation between the mean contributions of some OM sources and the concentrations of THg and MeHg in consumers.…”
Section: Links Between Hg Concentrations and Om Sourcesmentioning
confidence: 99%